Beyond Bakelite : Leo Baekeland and the business of science and invention - Mercelis, Joris, 1985- (London : MIT, 2020)
"I just want to say one word to you. Just one word. . . . Plastics." This line from the film The Graduate has come to symbolize the hubris, promise, and disappointment embodied in one of the world's most ubiquitous materials. At present, plastics are cheap, widely used, and durable. But that durability means that plastics persist in the environment for decades. Images of swaths of the ocean or beaches awash in plastic trash are regularly in the news. To address the ever-growing mass of plastic waste, entire countries are banning single-use plastic items, and solutions for recycling plastic effectively and for creating eco-friendly plastics are active fields of research. A little over a century ago, however, Leo Baekeland's invention of the first synthetic plastic-Bakelite-earned him the then-laudatory moniker "Father of Plastics" in the press.^
Bakelite proved to be an extremely useful product, with applications ranging from radio cabinets and electrical insulators to colorful Art Deco jewelry. Yet there is much more to Leo Baekeland's story than Bakelite. In his exploration of Baekeland's long career, Joris Mercelis traces Baekeland's life from his youth in Belgium through his education and immigration to the United States, and highlights Baekeland's other best-known invention, Velox photographic paper. Throughout, Baekeland maintained his American and European professional connections and continued to cross boundaries between the academy, business, and industrial research. While the book does not offer a full biography of Baekeland, Mercelis does use Baekeland's career as tool for examining the changing relations between (academic) science and industry, with special attention to intellectual property strategies and scientific entrepreneurship.^
Mercelis argues that a transatlantic perspective is necessary to appreciate the role of scientific entrepreneurship and intellectual property in the development of the science-industry nexus, and ultimately asks the question when and where to draw the line between the academic research and industrial pursuits"--
Includes bibliographical references and index.
Keywords: Baekeland, Leo Hendrik, -- 1863-1944.; Industrial chemists -- United States -- Biography; Inventions; Plastics -- History; Science and industry